Cross-linked carboxymethyl mung bean starch as pharmaceutical gelling agent and emulsion stabilizer - Nisit Kittipongpatana (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Sciences. All Rights Reserved. Objectives: This study aims to improve and expand the performance of carboxy methyl mung bean starch (CMMS) as a gelling agent and an oil-in-water (o/w) emulsion stabilizer via cross-linking reaction with dichloroacetic acid (DCA). Methods: Mung bean starch was carboxymethylated with chloroacetic acid and subsequently cross-linked with 0.1-10% DCA. Fifteen cross-linked carboxy methyl mung bean starches (CL-MBs) were obtained and the viscosity, clarity and pH of freshly-prepared gels, gels subjected to freeze-thaw cycles, and gels stored for 3 months at 8ºC and 45ºC were evaluated. The best CL-MB was selected and employed as gelling agent and as emulsion stabilizer in the pharmaceutical formulations of Capsicum gel and emulsion gel. Results: The gel formulation containing 5%w/w CMMS cross-linked with 8% DCA (CL-MB-8) as gelling agent was found to be comparable to the formulations using commercial gelling agents. CL-MB-8 was shown to tolerate up to 30%w/w alcohol with no significant effect to the gel characteristics. In the emulsion gel formulation, the use of 3%w/w CL-MB-8 helped stabilizing the o/w emulsion prepared from a mixture of Capsicum oil extract and water (1:3), with 2%w/w Tween80 as emulsifying agent. The formulation using wet-gum method yielded smooth, creamy gel with consistent color and good viscosity. Microscopic evaluation of the formulation revealed mostly small-sized o/w droplets evenly dispersed in the texture. Conclusion: Cross-linkage with DCA enhanced the viscosity of CMMS gel network and broadened the application of CMMS as gelling agent for herbal extract gel formulation with high alcohol content and also as a stabilizer for o/w emulsion.